а) у = 10х - 3
Выражение определено при любом х
х ∈ (-∞; +∞)
б) у =
x - 5 ≠ 0
x ≠ 5
x ∈ (-∞; 5) ∪ (5; +∞)
в) у = x² - 8x + 2
г) у =
x ∈ (-∞; 0) ∪ (0; 3) ∪ (3; +∞)
д) у =
x² - 1 ≠ 0
x² ≠ 1
x ≠ ±1
x ∈ (-∞; -1) ∪ (-1; 1) ∪ (1; +∞)
е) у =
x^2 + 1 ≠ 0
x^2 ≠ -1
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
а) у = 10х - 3
Выражение определено при любом х
х ∈ (-∞; +∞)
б) у =![\frac{1}{x-5} \frac{1}{x-5}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bx-5%7D)
x - 5 ≠ 0
x ≠ 5
x ∈ (-∞; 5) ∪ (5; +∞)
в) у = x² - 8x + 2
Выражение определено при любом х
х ∈ (-∞; +∞)
г) у =![\frac{4}{x(x-3)} \frac{4}{x(x-3)}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7Bx%28x-3%29%7D)
x ∈ (-∞; 0) ∪ (0; 3) ∪ (3; +∞)
д) у =![\frac{1}{x^2-1} \frac{1}{x^2-1}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bx%5E2-1%7D)
x² - 1 ≠ 0
x² ≠ 1
x ≠ ±1
x ∈ (-∞; -1) ∪ (-1; 1) ∪ (1; +∞)
е) у =![\frac{1}{x^2+1} \frac{1}{x^2+1}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bx%5E2%2B1%7D)
x^2 + 1 ≠ 0
x^2 ≠ -1
Выражение определено при любом х
х ∈ (-∞; +∞)
ВЫ МЕНЯ ВЫРУЧИЛИ !!!!